2012
DOI: 10.1155/2012/505274
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Pulmonary Hypertension: A Review of Pathophysiologic Mechanisms

Abstract: Pulmonary hypertension (PH) is a potentially life-threatening condition arising from a wide variety of pathophysiologic mechanisms. Effective treatment requires a systematic diagnostic approach to identify all reversible mechanisms. Many of these mechanisms are relevant to those afflicted with obesity. The unique mechanisms of PH in the obese include obstructive sleep apnea, obesity hypoventilation syndrome, anorexigen use, cardiomyopathy of obesity, and pulmonary thromboembolic disease. Novel mechanisms of PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 93 publications
3
72
0
12
Order By: Relevance
“…Obesity was found in several studies to be associated with hypoventilation and elevation in the pulmonary pressure [21]. It was estimated that BMI above 35 associated with prevalence of 31% in pulmonary hypertension [22]. In our study there was a positive correlation between the amount and the duration of the smoking with an increase in the pulmonary pressure.…”
Section: Discussionsupporting
confidence: 65%
“…Obesity was found in several studies to be associated with hypoventilation and elevation in the pulmonary pressure [21]. It was estimated that BMI above 35 associated with prevalence of 31% in pulmonary hypertension [22]. In our study there was a positive correlation between the amount and the duration of the smoking with an increase in the pulmonary pressure.…”
Section: Discussionsupporting
confidence: 65%
“…A prospective study looking at patients with OHVS admitted to the hospital showed a 23 % mortality at 18 months compared with 9 % in patients with obesity without hypoventilation (Nowbar et al 2004). The prevalence of PH in this population is higher than OSA alone, quoted to be as high as 50 % by some (Friedman and Andrus 2012;Kessler et al 1996). Additionally, many studies specifically looking at characteristics of patients with OSA and PH versus OSA without PH show that patients in the PH cohort have daytime hypercarbia Kessler et al 1996).…”
Section: Sleep-disordered Breathing and Chronic Hypoventilationmentioning
confidence: 87%
“…However with chronic hypoxemia, as seen in OHS, pulmonary artery remodeling occurs, and over times the pulmonary arterial hypertension transitions from a process of vasoconstriction to one of endothelial dysfunction, arterial wall thickening, and fibrosis. At this point the PH becomes much more difficult to reverse [8].…”
Section: Discussionmentioning
confidence: 99%